Reaction speed and attention of elite youth soccer goalkeepers: Do cognition and reaction influence each other? - Kovác, K.; Holienka, M.; Matušica, M.; Babic, M.; Skala, F.; Perácková, J. (Journal of Physical Education and Sport, 2025)
Problem Statement: Do cognition and reaction influence each other? Purpose: This research examined the level of cognitive performance and the interconnection with the disjunctive reaction speed in elite youth soccer goalkeepers. Soccer goalkeepers often need to have focused attention and a fast reaction when dealing with short-term problem-solving situations. In the research discussed in this article, we separately investigate the reaction speed to various stimuli and results of online cognitive tests. Research has only recently begun to focus on cognitive abilities of goalkeepers. The study involved 31 participants (184.8 ±4.7 cm; 77.6 ±7.1 kg) from elite Slovakian soccer academies selected from three youth categories: U16, U17, and U19. In this study, the level of disjunctive reaction abilities was measured using two tests: the response to the fast-generating visual stimuli (FGS) test and the response to the slow-generating visual stimuli (SGS) test. To evaluate the level of cognitive abilities, the Stroop test and the Attention test were used. The normative data as percentile ranges were highlighted in the selected test parameters. The significance level was established at p < 0.05. Results: The research has revealed that the ability of the players to react to SGS was correlated with the performance in the FGS test (r = 0.55 [CI 95; 0.24-0.76], p < 0.001). A significant correlation was found between performance in the Attention and Stroop tests (r = 0.58 [0.29-0.78]; p < 0.001). Conclusions: Low levels of correlation among reaction and cognitive tests revealed that reaction and cognition do not influence each other for soccer goalkeepers. Therefore, reaction and cognition should play a separate role in the testing of soccer goalkeepers.